2017
DOI: 10.1007/978-3-319-62701-4_14
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hospital Re-Admissions from Nursing Care Data of Hospitalized Patients

Abstract: Readmission rates in the hospitals are increasingly being used as a benchmark to determine the quality of healthcare delivery to hospitalized patients. Around three-fourths of all hospital re-admissions can be avoided, saving billions of dollars. Many hospitals have now deployed electronic health record (EHR) systems that can be used to study issues that trigger readmission.However, most of the EHRs are high dimensional and sparsely populated, and analyzing such data sets is a Big Data challenge. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Monsen et al 64 showed how specific interventions delivered by public health nurses during home visits were associated with decreased risks for pregnant women and their families suffering from social disadvantages and poverty. Lodhi et al 38 showed that SNT-coded nursing care plans are valuable in predicting hospital readmissions, which may help practitioners develop strategies to identify at-risk patients and potentially reduce healthcare costs in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Monsen et al 64 showed how specific interventions delivered by public health nurses during home visits were associated with decreased risks for pregnant women and their families suffering from social disadvantages and poverty. Lodhi et al 38 showed that SNT-coded nursing care plans are valuable in predicting hospital readmissions, which may help practitioners develop strategies to identify at-risk patients and potentially reduce healthcare costs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six (58%) studies analyzed nursing data coded with NANDA-I, [26][27][28] NOC, 29,30 NIC, [31][32][33] a combination of these terminologies (eg, NIC and NOC), [34][35][36] or the NNN set. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Fourteen (31%) studies used Omaha System, [52][53][54][55][56][57][58][59][60][61][62][63][64][65] while 4 (9%) used ICNP. [66][67][68] One (2%) study compared nursing data coded with NANDA-I and ICNP from different EHRs.…”
Section: Snts Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Other models are specifically designed for specific types of care. 13,14 There have been many different techniques used by models trying to predict hospital readmissions, such as support vector machines (SVMs), 15,16 classification trees (CTs), 7,15 and random forests (RFs), 9,17 along with techniques such as the LACE index, 18 which scores a patient's risk for readmission based on certain factors. One such method that has been used in predicting hospital readmission is Cox hazard regression analysis.…”
Section: Introductionmentioning
confidence: 99%